Characteristics of chronic rhinosinusitis patients at Ibnu Sina Hospital Makassar - Aulia, Rizka; Nurmadilla, Nesyana; Pratama, Ahmad Ardhani; Sanna, Andi Tenri; Utami, Dian Fahmi (Institute Of Computer Science (IOCS), 2025)
Background: Chronic rhinosinusitis is an inflammation of the nasal mucosa and paranasal sinuses that lasts for ? 12 weeks, involving sinusitis and rhinitis simultaneously. In Indonesia, the incidence data is uncertain, but a study in Palembang in 2019 showed the proportion of chronic rhinosinusitis in adults was 33.3%. Given the limited data, high prevalence, and impact of this disease, a study was conducted to analyze the characteristics of chronic rhinosinusitis patients at Ibnu Sina Hospital Makassar. Methods: This study used an analytic observational design with a cross-sectional approach, involving 83 subjects selected by consecutive sampling. Data taken from medical records included age, gender, clinical manifestations, antibiotic treatment, and sinus location. Univariate analysis was performed using Microsoft Excel. Results: The results of univariate analysis showed that most chronic rhinosinusitis patients were aged 17-25 years (41.27%), followed by patients aged 26-35 years (26.98%). Male patients slightly outnumbered females, with 50.79% male and 49.21% female. The most common clinical manifestations were facial pain (63.49%), nasal congestion (53.97%), and headache (63.49%), while less common symptoms included cough (11.11%) and bad breath (4.76%). In terms of antibiotic treatment, cefadroxil was the most commonly administered (33.3%), followed by ceftriaxone (31.7%) and cefixime (24.2%). Regarding the site of sinus involvement, multi-sinusitis was the most common (60.5%), followed by unilateral sinusitis (34.2%) and pansinusitis (5.26%). Conclusion: Chronic rhinosinusitis at Ibnu Sina Hospital Makassar was most common in males aged 17-25 years, with facial pain as the main symptom, multi-sinusitis as the most common location, and cefadroxyl and ceftriaxone as the main antibiotics used.